Serum specific IgE responses to inhalant allergens sensitization (Medical Journal of Indonesia, 2017)
Background: Serum specific immunoglobulin E (ssIgE) sensitization to common inhalant allergens has not been studied in Indonesia. This study aimed to evaluate specific IgE production of common inhalant allergens in patients with asthma and/or allergic rhinitis in Jakarta, Indonesia.Methods: This was a cross-sectional study in adult patients with respiratory allergy from September to December 2016 at Cipto Mangunkusumo Hospital, Jakarta. Patients were included if they showed at least one positive skin prick test (SPT) to environmental allergens. Serum specific IgE was assayed by using multiple allergosorbent methods. Inhalant allergens tested were dust mites, pollen, cockroach, animal dander, and mould. Serum IgE level more than 0.35 kU/L was considered positive.Results: One hundred subjects were enrolled (76% women). Dust mites made up 75% of sensitization, followed by cat/dog (31%), cockroach (27%), pollen (24%), and mould (6%). Almost all patients sensitized to cockroach, pollen, cat/dog epithelia and mould were also co-sensitized with dust mites. Twenty two percent of patients were negative to all tested allergens.Conclusion: IgE-sensitization to inhalant allergens varies widely in respiratory allergic patients. House dust and storage mites are the most common allergens. About one-fifth of the subjects did not show specific-IgE sensitization. Thus, this test should always be combined with SPT to diagnose allergy.